2020
DOI: 10.3390/app10020470
|View full text |Cite
|
Sign up to set email alerts
|

Processed Fruiting Bodies of Lentinus edodes as a Source of Biologically Active Polysaccharides

Abstract: Water soluble polysaccharides (WSP) were isolated from Lentinus edodes fruiting bodies. The mushrooms were previously subjected to various processing techniques which included blanching, boiling, and fermenting with lactic acid bacteria. Therefore, the impact of processing on the content and biological activities of WSP was established. Non-processed fruiting bodies contained 10.70 ± 0.09 mg/g fw. Boiling caused ~12% decrease in the amount of WSP, while blanched and fermented mushrooms showed ~6% decline. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…During the process of fermentation, the extracts of Ganoderma lucidum mostly composed of polysaccharides and have the ability to increase the abundance of Bifidobacteria ( Yamin et al, 2012 ); Zhang et al (2017) demonstrated that the Ganoderan is extracted from the Ganoderma sp. and having β-(1→3)-D-glucans with β-(1→6)-D-glucopyranosyl branches and the molecular weight is around 1.2 × 10 6 Da to 4.4 × 10 6 Da ( Üstün et al, 2018 ; Ziaja-Sołtys et al, 2020 ). Additionally, due to the daily supplementation of Ganoderma lucidum polysaccharide strain, the abundance of bacteria like Roseburia , Lachnospiraceae , and Lactobacillus with health benefits to host enhanced significantly ( Li et al, 2016 ).…”
Section: Active Metabolite From Mushroommentioning
confidence: 99%
“…During the process of fermentation, the extracts of Ganoderma lucidum mostly composed of polysaccharides and have the ability to increase the abundance of Bifidobacteria ( Yamin et al, 2012 ); Zhang et al (2017) demonstrated that the Ganoderan is extracted from the Ganoderma sp. and having β-(1→3)-D-glucans with β-(1→6)-D-glucopyranosyl branches and the molecular weight is around 1.2 × 10 6 Da to 4.4 × 10 6 Da ( Üstün et al, 2018 ; Ziaja-Sołtys et al, 2020 ). Additionally, due to the daily supplementation of Ganoderma lucidum polysaccharide strain, the abundance of bacteria like Roseburia , Lachnospiraceae , and Lactobacillus with health benefits to host enhanced significantly ( Li et al, 2016 ).…”
Section: Active Metabolite From Mushroommentioning
confidence: 99%
“…Its chemical structure consists of a β-1, 3 glucopyranoside main chain with β-1, 6 glucopyranoside branched chain [ 61 ]. This β-glucan structure of lentinan was shown to mediate anticancer effect in vitro and in vivo [ 62 ]. There is evidence to suggest that the structural conformation of lentinan is critical for its anticancer activity; Indeed, the triple-helix conformation of lentinan had a higher anticancer effect compared to its single flexible chain structure [ 63 ].…”
Section: Anticancer Effects Of Shiitake and Its Main Medicative Compounds/extractsmentioning
confidence: 99%
“…The antibacterial, antiviral, antioxidant, or antitumor effects of plant and fungal substances are widely known. Many of them are also used to treat human and animal gastrointestinal diseases caused by parasites [ 1 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%